EL TRAZADO VIARIO DE CARTHAGO-NOVA. (NUEVOS HALLAZGOS DEL DECUMANO MAXIMO) - Miquel Santed, L. E. de (Anales de Prehistoria y Arqueología, 1987)
The modern archaeological research in building plots of the Cartagena center, are giving in the last years some new tracks of the roman streets of the town. In this work, are studying two of the most recent finds. We make their description and analize the road axis they belong. We can reconstitute the Carthago-Nova Decumanus Maximo location through them. Also, we make a complete review on the researchs about the roman streets in Cartagena; we rectify some untrue interpretations of the later archaeologist and give some new suggestions of them.